USE THE MODELS AND DATA BALANCES OF THE PANEL TO ESTIMATE THE IMPACT OF THE INFLATION AND THE VALUE OF THE MERCHANDISE FROM THE BANKS OF COMMERCIAL MARKETS IN IRAQ (World Economics and Finance Bulletin, 2025)
This study aims to demonstrate inflation and its impact on market value using audited annual financial statements of five Iraqi commercial banks . To realize the purpose of this study, previous studies and the theoretical framework were relied upon, as well as the annual data on the market value of banks published on the website of the Iraq Stock Exchange, and the annual inflation data published on the websites of the Central Bureau of Statistics . There is a significant and important effect of distension on market stock prices and a direct connection between the independent variable (inflation) and the dependent variable (mart value) . In light of the extracted results, this study presented a set of recommendations directed to future researchers and management of frim tied on the Iraqi Stock market, and to the mart management, the most important of which is the need to increase the level of awareness of individual traders of inflationary fluctuations in terms of their impact on the performance and movement of stocks, and knowledge to help them develop strategies for their investment portfolios, while encouraging an increase in the number of investors .
Keywords: Inflation; Market Value; Stock Market